Dabble Games as a Media to Improve Listening Skills for Elementary School Students - Dewi Ikrimah Agustin (Saniya Institute, 2023)
This study aims to explore the effectiveness of dabble games as a medium for improving the listening skills of elementary school students. Experimental research methods are used to collect data from students involved in dabble game activities. The results of the research show a significant improvement in student listening abilities after participating in these games. These findings show that Dabble can be an effective tool for improving elementary-school students' listening abilities and making a positive contribution to their language learning. The practical implications of this study provide new insights into the development of interesting and interactive learning methods to improve listening skills at the elementary education level.